A Flat Asymptotic Frictionless Contact Subject to Normal Load and Bending Moment. (21st October 2014) - Shao, G.-Q.; Hong, J.; Jiang, X.-J.; Zhu, L.-B.; Chen, X.; Zhu, Y.-S.
Abstract : A calculation model is put forward to analyze the interfacial response of an elastic frictionless punch, pressed normally into a half-plane, and subject to bending moment throughout this paper to observe the important effect that different normal loads and bending moments on the contact pressure distribution and contact deformation. Results for the detailed considerations have been given to the specific different cases of η c . A characteristic response of the punch to a surplus bending moment has been found. The small differences can be observed between both methods show characteristic features of the FEM model and the theoretical model. The presented numerical results illustrate the influences of the normal load and bending moment on the contact stresses. The results obtained can be used to analyze the crack nucleation in fretting when the punch is acted upon by the normal force and the bending moment.